Comparative Efficacy of Zolpidem and Nigella Sativa in Treatment of Sleep Disorder and Vasomotor Symptoms in Menopausal Women of Women's General Hospital - Mojgan Asadi; Fatemeh Molavi; Mostafa Qorbani; Fatemeh Davari Tanha (Tehran University of Medical Sciences, 2020)
Objective: To evaluate the efficacy of Zolpidem and Nigella sativa compared to placebo in treatment of sleep disturbance in healthy postmenopausal women. Menopause is a period that diagnosed after 12 months of amenorrhea and is characterized by a group of symptoms that include irregular menses; vasomotor and urogenital symptoms. The effects of non-hormonal therapies are being widely researched on menopause symptoms. There has been no study to compare Zolpidem and Nigella sativa versus placebo. Materials and methods: In this double-blind, placebo controlled trial, we compared the effect of Zolpidem with Nigella sativa and placebo in reducing sleep quality in 60 menopausal women. The prior and the later results were compared. We divided the patients into three groups after history taking and physical examination and filling the Pittsburgh questionnaire. Each group received their medication as the following order: Group A: Zolpidem, Group B: Nigella sativa, Group C: placebo. The first group received Zolpidem with the dose of 5 mg for 8 weeks. The second group received Nigella sativa with the dose of 600 mg for 8 weeks. The third group received placebo for 8 weeks. After two months, the Pittsburg questionnaire was filled again. Results: In the nigella sativa group, we had not significant improvement in sleep quality (p =0.07), hot flashes (p =0.15), palpitation (p =0.56) and night sweets (p =0.08).  In zolpidem group, we have seen lack of improvement of hot flashes (p =0.73), and palpitation (p =0.36), which are nonsignificant statistically according to p values, but in zolpidem group, we had significant improvement in sleep quality (p =0.01), and night sweats (p =0.049). Conclusion: It seems that zolpidem has some effect on improving the quality of sleep in postmenopausal women. zolpidem also is good for night sweats. Nigella sativa was not effective in vasomotor symptoms and sleep quality.